Physical Activity Levels of a Multi-Ethnic Population of Middle-Aged Men Living in Saudi Arabia and Factors Associated With Physical Inactivity - AlFaris, Nora A.; Alshwaiyat, Naseem M.; AlTamimi, Jozaa Z.; Alagal, Reham I.; Al-Jamal, Hamid A.; AlKehayez, Nora M. (International Journal of Public Health, 2022)
Objectives: This study investigated physical activity levels and factors related to physical inactivity in a multi-ethnic population of middle-aged men living in Saudi Arabia. Methods: This is a cross-sectional study in which 1,800 men aged 36-59 years old from Riyadh, Saudi Arabia participated. The Global Physical Activity Questionnaire was used to assess the physical activity levels. The weight and height were measured and used to calculate the body mass index. Results: Among all participants, 35.3% are physically inactive. The participants with the lowest and highest rates of physical inactivity were from the Philippines (15.5%) and Saudi Arabia (57.8%), respectively. This study suggests that the risk of physical inactivity among participants is positively or negatively affected by various factors, including nationality, residency period in Saudi Arabia, living with/without family, education level, monthly income, and body mass index. Conclusion: The prevalence of physical inactivity is relatively high among middle-aged men in Saudi Arabia. The findings revealed significant differences in physical activity levels based on nationality, other sociodemographic variables and body weight status.